Sustainability, Where Are Thou? Assessing Kazakhstani University Mission Statements - Frigerio, Alberto (Journal of Education for Sustainability and Diversity, 2025)
Over the last decade, higher education institutions have made significant strides in promoting sustainability and social responsibility. However, the integration of these principles into university mission statements remains insufficient. While universities are advancing in practice, they often fall short of formally embedding these values into their core strategies. This study examines the incorporation of sustainability and social responsibility within the mission statements of 91 Kazakhstani universities. Through word frequency and thematic analysis, key themes and priorities of Kazakhstani higher education institutions are identified. The results highlight a focus on traditional aspects such as “leadership and competitiveness” (71.5%), “innovation and technology” (58.3%), and “education quality” (39.5%). In contrast, “sustainability” is mentioned in only 7.7% of the statements, indicating it is not yet a strategic priority, while “social responsibility” appears in 23.1% of cases, with a notable emphasis on societal benefits and human capital development. These findings suggest a predominant focus on immediate national development goals, potentially at the expense of global educational trends in sustainability. To enhance international competitiveness and better prepare students for global challenges, Kazakhstani universities should more thoroughly integrate sustainability into their strategic frameworks.